Simulation Use in Acute Care Hospitals in the United States. Issue 5 (September 2018) - Harper, Mary G.; Gilbert, Gregory E.; Gilbert, Marie; Markey, Linda; Anderson, Krista
Abstract : Three national nursing associations formed a collaborative partnership to research simulation use in acute care hospitals in the United States and military hospitals abroad. An electronic survey was used to determine simulation modalities used, participants engaged, space allocation, purposes of use, commonly taught skills, logistics, and barriers to use. Data from 521 respondents revealed widespread use of a variety of simulation modalities. However, use of this educational strategy could be expanded to patients and families.